Cervical cancer data and data systems in limited-resource settings: Challenges and opportunities - Drummond, Jennifer L. (2017)
Appropriate collection and use of health information is critical to the planning, scaling up, and improvement of cervical cancer programs. The health information systems implementation landscape is unique to each country; however, systems serving cervical cancer programs in low-resource settings share characteristics that present common challenges. In response, many programs have taken innovative approaches to generating the quality information needed for decision making. Recent advances in health information technology also provide feasible solutions to challenges. This article draws from the experiences of the authors and from current literature to describe outstanding challenges and promising practices in the implementation of cervical cancer data systems, and to make recommendations for next steps. Recommendations include engaging all stakeholders—including providers, program managers, implementing partners, and donors—in promoting national, district, and community information systems; building on existing systems and processes, as well as introducing new technologies; and evolving data collection and data systems as programs advance.